A Systematic Review of Development of Environment-Friendly Roads in Mountains of Rural Nepal - Kc, Dhanendra; Gyawali, Saroj; Thapa, Bijay (Journal of Engineering Issues and Solutions, 2026)
This literature review explores the effects of climate change on eco-friendly road construction in Nepal’s mountainous regions, examining 45 peer- evaluated studies to judge climatic influences, adaptation techniques and framework flexibility. Important discoveries specify a notable temperature rise of 0.06 degree Celsius annually and a precipitation decrease of 2.1 mm annually, directing to instability of soil, growth in landslide frequency up to 15% and decrease in the lifespan of bioengineered roads by 20%. Monsoon flood and winter drought worsen the problems, making almost 12% of rural roads almost difficult to walk, which affects the 8% of the rural populations to get the services. Proper transformation methods, such as bioengineering with vetiver plants, proper sewage system and climate stability infrastructures, have decreased the soil erosion by almost 30% and increased the longevity of the roads by 25% in rural areas. Nevertheless, execution is compelled to be delayed due to less funds, limited technical expert manpower and poor plans and policies by the government. The uncertainty index points out the vulnerable districts like Mustang and Dolpa, indicating the necessity of region-specific action plans. This review advises targeted funding, community training and policy support to increase the stability of roads, with suggestions to the neighboring South Asian countries who are facing similar problems. Intervals in long-term beneficial data and socio-economic effect evaluation highlights the necessity for future investigation to support eco-friendly infrastructure development in Nepal.